PEMANFAATAN MEDIA LAGU SEBAGAI PENDUKUNG MATA PELAJARAN MATEMATIKA MATERI PENJUMLAHAN KELAS I SD NEGERI 040454 PECEREN - Rifka Afriani Br Tarigan; Wisno Saputra Sembiring; Nurlia Ginting (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of mathematics learning on addition material using song media and to analyze student responses to the use of such media in Grade I at SD Negeri 040454 Peceren. The main problem in this research is the low motivation and students' difficulty in understanding abstract addition concepts through conventional methods. The research method used is descriptive qualitative. The research subjects consisted of 26 first-grade students at SD Negeri 040454 Peceren. Data collection techniques included observation, interviews, and documentation. Data validity was ensured through technical and source triangulation techniques. The results of the study indicate that the use of the song media “Ayo Berjumlah,” adapted from the melody of “Lihat Kebunku” and supported by number block manipulatives, is effective in improving students’ understanding of addition concepts. The implementation of the learning process creates a joyful learning atmosphere that helps reduce students’ anxiety toward mathematics. This is evidenced by the improvement in students’ learning outcomes as well as very positive responses, shown through increased enthusiasm, cheerfulness, and self-confidence during the learning process.